Unified method for optimal power flow of AC/DC system with PET based on extended branch model. Issue 16 (18th December 2018) - Sun, Yingyun; Hu, Liping; Malik, Sarmad Majeed; Chen, Naishi; Pu, Tianjiao
Abstract : Compared to traditional transformer, power electronic transformer (PET) has a better control ability as it can manage the terminal power independently. This makes it very promising for modern power distribution systems with high penetration of renewable energy. However, the unique structure of PET increases the coupling between AC and DC network, which enhances the complexity of the traditional alternating iterative method in an AC–DC network. Since the structure of PET is based on power electronics, the power losses will influence the OPF results and have to be taken into account. This paper proposes a novel extension branch model with an accurate PET power loss model that can solve the AC–DC power flow problem in a unified way. In this method, a branch model of PET with power loss is first established. The AC and DC branches are then combined to generate an extended branch model of the whole AC–DC network. An AC–DC hybrid test system connected by two 3‐port PET is used to verify the effectiveness of the proposed model via simulations. The results show that this method has a superior convergence speed than the alternating iterative model.